A Prospective Stroke Register in Sierra Leone: Demographics, Stroke Type, Stroke Care and Hospital Outcomes - Youkee, Daniel; Deen, Gibrilla; Barrett, Edward; Fox-Rushby, Julia; Johnson, Israel; Langhorne, Peter; Leather, Andrew; Marshall, Iain J.; O'Hara, Jessica; Rudd, Anthony; Sama, Albert; Scott, Christella; et al. (Frontiers in Neurology, 2021)
Introduction Stroke is the second most common cause of adult death in Africa. We report the characteristics of stroke in Freetown, Sierra Leone. Methods A prospective observational register recorded all patients 18 years and over with stroke between May 2019 and April 2020. Stroke was defined according to the WHO criteria. Pearson’s chi squared test was used to examine associations between categorical variables and unpaired t-tests for continuous variables. Multivariable logistic regression was performed to explain in-hospital death, we report odds ratios (OR) and 95% confidence intervals. Results 385 strokes were registered, 315 (81.8%) were first in a lifetime events. Mean age was 59.2 (SD 13.8) and 187 (48.6%) were male. 327 (84.9%) of strokes were confirmed by CT scan. 231 (60.0%) were ischaemic, 85 (22.1%) intracerebral haemorrhage, 11 (2.9%) subarachnoid haemorrhage and 58 (15.1%) undetermined stroke type. The median Barthel Index before stroke was 100 (IQR 100-100) and median National Institute of Health Stroke Scale on presentation was 17 (IQR 9-25). Haemorrhagic strokes compared to ischaemic strokes were more severe, 20 (IQR 12-26) vs 13 (IQR 7-22) (p<0.001), and occurred in a younger population, mean age 52.3 (SD 12.0) vs 61.6 (SD 13.8) (p<0.001), with a lower level of educational attainment 28.2% vs 40.7% (p=0.04). The median time from stroke onset to arrival was 25 hours (IQR 6-73). Half of the patients (50.4%) sought care at another health provider before coming to Connaught Hospital. 151 patients died in hospital (39.5%). 43 deaths occurred within 48 hours of arriving at hospital and the median time to death was 4 days (IQR 0-7 days). 49.6% of patients had ≥1 complication, 98 (25.5%) pneumonia, 33 (8.6%) urinary tract infection. Male gender OR 3.33 (1.65 - 6.75), pneumonia OR 3.75 (1.82 – 7.76), subarachnoid haemorrhage OR 43.1 (6.70-277.4) and undetermined stroke types OR 6.35 (2.17– 18.60), were associated with higher risk of in-hospital death. Discussion We observed severe strokes occurring in a young population with high in hospital mortality. Further work to deliver evidence-based stroke care is essential to reduce stroke mortality in Sierra Leone.